Expecting Better? How Young People Form Their Earnings Expectations - Marta Favara; Paul Glewwe; Catherine Porter; Alan Sanchez (Institute of Labor Economics (IZA), 2021)
Education choices are made based on the expected returns to schooling. If individuals are badly informed, they may make inefficient choices. We directly elicit young people's subjective expectations at the age of 14-15 about earnings under different educational scenarios and find these predict university enrolment by the age of 18-19. Females expect lower earnings than males, likely anticipating the reality of the labour market. Living in a poorer household, weaker numeric skills and lower self-efficacy are also associated with lower expected returns to education. Comparing expectations with the actual earnings from a nationally representative sample of individuals matched by sex, region and place of residence, we find that expectations for earnings upon completing secondary education closely match observed earnings, while there is a tendency to overestimate the returns to completing a university degree. These results hold for both males and females although with considerable variation across regions and population subgroups.
Keywords: I2; J22; J24; 330; subjective expectations; earning realizations; Young Lives; Peru